Calcio e Esports: un connubio ideale - Alfredo de Martini (SHARE Press, 2021)
The Covid-19 pandemic suspended or canceled sporting events, disrupted competitive seasons, changed tournament calendars, and reduced revenues to zero. While traditional sports have come to a halt, the data highlights how, conversely, the number of following esports events on streaming platforms such as Twitch has increased. Consequently, it is understandable that - never more than now - traditional sport uses digital, discovering new ways of entertainment. The research tries to understand what can be, once esports are introduced into the business strategies of sports companies, their opportunities for fan engagement, brand awareness and social reaction growth. The paper presents the results of a qualitative-qualitative research characterized by two phases: the first, involves interviews with privileged witnesses, intends to identify the brand policies and marketing strategies of sports clubs; the second is a quantitative analysis aimed at estimating the engagement, awareness and reaction rates generated by the esports created by the Federation and the football club. The goal is to investigate the impact of esports on brand identity and their impact on possible future opportunities for the development of sports entertainment.